Enhancing garbage fee compliance: Insights from a Slovak municipality - Caplanova, Anetta; Sirakovova, Eva; Szakadatova, Estera (Economics and Business Review, 2024)
Tax avoidance and tax evasion remain critical challenges for central or local governments and municipalities. This non-compliance also represents an ethical issue since individuals who benefit from publicly provided services do not contribute to their financing as they are legally required. The study aimed to test whether the use of behavioural interventions would reduce the number of non-payers of the garbage collection fee in the city of Hlohovec, Slovakia. The experiment was carried out by distributing leaflets to households with permanent residence in Hlohovec. The subjects of the experiment were randomly divided into three groups. Households in the control group (number of households is 1,718) did not receive any leaflets, households in the first intervention group (number of households is 1,721) received a leaflet containing a social norm, and households in the second intervention group (number of households is 1,625) received a leaflet containing a deterrent message.